Soffa på jobbet? - Andersdotter, Gunnel (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2001)
A group of software designers, all young men, want to buy sofas and television sets for the office. They want to use these as combined places and spaces for taking short breaks in, but also for work. The latter is something they already practice when bringing work home after office hours. The proposed introduction of these everyday pieces of furniture and technology into the project based development work is not granted. A process of negotiation starts between the young men and the department management. The article explores the implicit and explicit meanings that this process brings out, mainly what is considered as acceptable place and time for relaxation at work. An important issue is how the arguments link to the design and configuration of the office space, especially concerning sofas and chairs. But also how the arguments link to models and rhetorics concerning the organization and company culture. Marine metaphors are used as strong rhetorical means — implemented in talk, on paper, on the web, as well as in the architecture and furnishing — in order to, as management puts it, "sail" successfully on "the infocom sea".